Pengembangan Produk Pie Kacang Merah Tinggi Kalsium Menggunakan Tepung Kepala Ikan Lele dan Tepung Chia Seeds - Rimbawan, Rimbawan; Nasution, Zuraidah; Riana, Nidya Ulfah (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2024)
This study aims to develop a pie product substituting wheat flour with composite flour from catfish head flour and chia seeds flour as an alternative high-calcium product. The experimental design used was a completely randomized design with four percentages of wheat flour substitution with composite flour (100:0%, 93:7%, 86:14%, 79:21%). The analysis used was organoleptic test (acceptance test), physical analysis (color and texture), nutritional profile analysis (proximate, calcium, and calcium bioavailability). Data were analyzed using One-Way ANOVA and independent sample T-test. The level of pie hardness, ash content, protein, fat, calcium and calcium bioavailability increased along with the increasing use of composite flour, but carbohydrate content decreased. Substitution of wheat flour with composite flour tended to decrease panelist’s preference for pie color, but did not affect panelist’s assessment of aroma, texture, taste, and overall acceptance. Substitution (86:14%) of wheat flour with composite flour was chosen as the best formula with the results of nutritional content of 13.98% water content, 2.94% ash content, 11.47% protein, 25.57% fat, 46.04% carbohydrate, and calcium content of 541.13 mg/100 grams. The results of this study indicate that substitution of wheat flour with a mixture of catfish head flour and chia seeds flour in pies can provide an alternative product of high calcium. Penelitian ini bertujuan untuk mengembangkan produk pie substitusi tepung terigu dengan tepung komposit dari tepung kepala ikan lele dan tepung chia seeds sebagai alternatif produk tinggi kalsium. Rancangan percobaan yang digunakan adalah rancangan acak lengkap dengan empat persentase substitusi tepung terigu dengan tepung komposit (100:0%, 93:7%, 86:14%, 79:21%). Analisis yang digunakan adalah uji organoleptik (uji penerimaan), analisis fisik (warna dan tekstur), analisis kandungan gizi (proksimat, kalsium, dan bioavailabilitas kalsium). Data dianalisis menggunakan One-Way ANOVA dan independent sample T-test. Tingkat kekerasan pie, kadar abu, protein, lemak, kalsium dan bioavailabilitas kalsium meningkat seiring dengan peningkatan penggunaan tepung komposit, tetapi kadar karbohidrat menurun. Substitusi tepung terigu dengan tepung komposit cenderung menurunkan kesukaan panelis terhadap warna pie, tetapi tidak memengaruhi penilaian panelis terhadap aroma, tekstur, rasa, dan penerimaan keseluruhan. Substitusi (86:14%) tepung terigu dengan tepung komposit dipilih sebagai formula terbaik dengan hasil kandungan gizi sebesar 13,98% kadar air, 2,94% kadar abu, 11,47% protein, 25,57% lemak, 46,04% karbohidrat, dan kandungan kalsium sebesar 541,13 mg/100 gram. Hasil penelitian ini menunjukkan substitusi tepung terigu dengan campuran tepung kepala ikan lele dan tepung chia seeds pada pie dapat memberikan produk alternatif tinggi kalsium.